The Lexeme вызов in the Contemporary Russian Language: The Extension of Semantic Structure - Pavel Vladimirovich Shakin (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2018)
This article studies the extension of the semantic structure of the Russian lexeme вызов influenced by the English lexeme challenge. Based on explanatory Russian and English dictionaries, the author carries out componential analysis of lexical and semantic variants of the two lexemes. The aim of the analysis is to identify the reasons behind the emergence of a new lexical and semantic variant in the Russian language as related to the semantics of challenge. The comparison demonstrates that the Russian and English lexical units denominate the situation of language activity between two communicants connected by causative relations. Moreover, a new lexical and sematic variant is identified in the structure of lexeme challenge reflecting a special character of a causative situation where the causator is an inanimate object task, which induces an animate object to initiate a certain activity, pursuing a special goal meant to test their abilities and achieve a successful result. Due to shared lexical and semantic variants in the meanings of the two words, the semantic structure of the word вызов extends. During the componential analysis of вызов, the author detects new unique differential semes, such as “personal resource”, “newness / topicality”, “positive attitude” characteristic of the semantic structure of the lexeme challenge, which testifies to the linguocultural influence of the English word. Additionally, the seme “positive attitude” does not recur on a regular basis but is sporadic which is determined by the asymmetry of linguistic worldviews. The fact that new semantic components of lexeme вызов are actualised is verified by corpus-based research. The change of causative relations in the semantic structure leads a native speaker to adopt a new frame of reference which is not typical of Russian mentality, testing the person’s limit of ability facing new problems.